Genetic diversity of Epimedium elatum (Morren & Decne) revealed by RAPD characterization - Qazi Pervaiz Hassan, Sajad Ahmad Lone; Gupta, Suphla (Current Botany, 2018)
Epimedium elatum (Morren & Decne) is a rare perennial monotypic medicinal herb of Berberidaceae family, endemic to high altitude shady coniferous forests of Northwestern Himalayas in India. Traditionally, it has been used in local health care system for treatment of many ailments. In the present study, a total of ten RAPD markers were used for assessment of genetic diversity in twenty accessions of E. elatum, collected from diverse ecozones in Jammu and Kashmir. Ten primers amplified a total of 100 polymorphic bands with average of 10 bands per assay unit. Primer OPO-07 generated maximum number of bands (15) & produced highest polymorphic information content (0.39), marker index (5.96) and resolving power (8.9), thereby distinguishing E. elatum genotypes. The study showed moderate level of genetic polymorphism in twenty accessions of E. elatum. RAPD data set revealed association between genetic diversity and eco-geographic distribution of most E. elatum genotypes, and thereby proved useful tool for their genetic/molecular characterization. There is an urgent need for developing quick conservation strategies to save its natural germplasm from extinction in the Northwestern Himalayas.